Unveiling the Cloak: Kernel Theory Use in Design Science Research - Möller, Frederik; Schoormann, Thorsten; Strobel, Gero; Hansen, Magnus Rotvit Perlt (ICIS 2022 Proceedings, 2022)
Theory is an essential part of design research and helps us to explain what we see or guide what we design. In the paper, we shed light on how kernel theories are used in developing design principles in Design Science Research (DSR). We do this by reporting on a systematic literature review, from which we have extracted a set of six mechanisms to operationalize kernel theory. Each mechanism consists of an activity (e.g., “transform to” or “derive from”) and an application point (e.g., meta-requirements or design principles) representing wherein the chain of concepts the kernel theory was used. The paper reflects on what we have learned about the use of kernel theories and translates this into recommendations and issues for further research. We provide researchers with guidance to use kernel theories more efficiently and give a big picture of the possibilities of kernel theory operationalization.
Keywords: Design principles; kernel theory; design theory; design science research